The influence of macroeconomic indicators on consumer's decisions - Zhuk, Mykola (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The purpose of this article is to analyze the infl uence of macroeconomic indicators on consumer’s decisions. The author tried to compile a list of macroindicators that would be most useful for a consumer in his decision making. Also, he tried to show the way these indicators infl uence consumption, using the example of EU statistical data.
Keywords: macroeconomic indicators; consumer; decision